ANALISIS EFEKTIVITAS METODE PENYUSUTAN AKTIVA TETAP PADA LABA PERUSAHAAN : STUDI KASUS : PT. LABBERU TAHUN 2011-2013 - Salesti, Jayana (MEASUREMENT : Jurnal Program Studi Akuntansi, 2015)
The purpose of a company is to achieve optimal profits for the investment that has been invested in the company. One of the investments is the Fixed Assets which is used in the normal activity of a company and has economic age for more than a year. To achieve that purpose, the effective management and the exact needs in using, maintaining even recordings are needed.The amount of fixed assets depreciation expenses impacts the amount of profits earned by a company. This thesis is trying to discuss about the effect of the depreciation method chosen to the calculation of the profit.Keywords :depreciation method, depreciation expenses, fixed assets, profit